Microsatellite organization in the B Chromosome and A Chromosome complement in Astyanax (Characiformes, Characidae) species - Piscor, Diovani [UNESP]; Parise-Maltempi, Patricia P. [UNESP] (Karger Publishers, 2016)
The organization of microsatellites in B and sex chromosomes has been linked to chromosomal evolution in a number of animal groups. Here, the chromosomal organizations of (CA)15, (GA)15, (CG)15, (GACA)4, and (GATA)8 microsatellites were examined in several Astyanax species with different diploid numbers: Astyanax mexicanus (2n = 50 + 1 B chromosome), A. altiparanae (2n = 50), A. marionae (2n = 48), A. fasciatus (2n = 46), and A. schubarti (2n = 36). The (CA)15 and (GA)15 microsatellites were dispersed across the chromosomes of A. altiparanae and A. fasciatus but were also observed as clusters (CA and GA for A. altiparanae, and CA for A. fasciatus). In A. marionae and A. schubarti, the (CA)15 and (GA)15 microsatellites were dispersed but were also observed as clustered signals and coincident with heterochromatic regions. In all 4 of these species, the (CG)15 and (GACA)4 microsatellites were dispersed across chromosomes, and the (GATA)8 microsatellite was co-localized with 5S rDNA. In A. mexicanus, the (CA)15, (GA)15, (CG)15, (GATA)8, and (GACA)4 microsatellites were weakly detected and dispersed across the chromosomes of the A complement. On the B chromosome, signals for the different microsatellites were weak, strong, absent, weak, and absent, respectively. The distribution of microsatellites and the locational relationship between microsatellites and 5S rDNA are discussed, and a possible evolutionary pathway is proposed for microsatellites in Astyanax.
Keywords: Astyanax schubarti; Chromosome evolution; Heterochromatin; Mexican blind cavefish; Repetitive DNA